Distinct roles of two RDL GABA receptors in fipronil action in the diamondback moth (Plutella xylostella). (13th January 2021) - Li, Ben‐Jie; Wang, Kun‐Kun; Chen, Dong‐Ping; Yan, Ying; Cai, Xu‐Ling; Chen, Hui‐Min; Dong, Ke; Lin, Fei; Xu, Han‐Hong
Abstract: The phenylpyrazole insecticide fipronil blocks resistance to dieldrin (RDL) γ‐aminobutyric acid (GABA) receptors in insects, thereby impairing inhibitory neurotransmission. Some insect species, such as the diamondback moth ( Plutella xylostella ), possess more than one Rdl gene. The involvement of multiple Rdl s in fipronil toxicity and resistance remains largely unknown. In this study, we investigated the roles of two Rdl genes, PxRdl1 and PxRdl2, in P. xylostella fipronil action. In Xenopus oocytes, Px RDL2 receptors were 40 times less sensitive to fipronil than Px RDL1. Px RDL2 receptors were also less sensitive to GABA compared with Px RDL1. Knockout of the fipronil‐sensitive PxRdl1 reduced the fipronil potency 10‐fold, whereas knockout of the fipronil‐resistant PxRdl2 enhanced the fipronil potency 4.4‐fold. Furthermore, in two fipronil‐resistant diamondback moth field populations, PxRdl2 expression was elevated 3.7‐ and 4.1‐fold compared with a susceptible strain, whereas PxRdl1 expression was comparable among the resistant and susceptible strains. Collectively, our results indicate antagonistic effects of Px RDL1 and Px RDL2 on fipronil action in vivo and suggest that enhanced expression of fipronil‐resistant PxRdl 2 is potentially a new mechanism of fipronil resistance in insects. Abstract : The phenylpyrazole insecticide fipronil blocks resistance to dieldrin (RDL) γ‐aminobutyric acid (GABA) receptors in insects, thereby impairing inhibitory neurotransmission. Some insect species, such as the diamondback moth ( Plutella xylostella ), possess more than one Rdl gene. The involvement of multiple Rdl s in fipronil toxicity and resistance remains largely unknown. In this study, we investigated the roles of two Rdl genes, PxRdl1 and PxRdl2, in P. xylostella fipronil action.